NILAI-NILAI DAKWAH ISLAM DALAM TRADISI NGAROT DI DESA LELEA KECAMATAN LELEA KABUPATEN INDRAMAYU - Malik, Saeful; Askolani, Muhammad; Jalaludin, Jalaludin (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2021)
Da'wah values are derivatives or developments from sources of Islamic teachings, namely the Qur'an and Sunnah. Therefore, Abdul Basit grouped them into three types, namely; Universal values, cultural values and personal values. The three groups produced several derivatives of da'wah values as follows, namely the value of discipline, the value of honesty, the value of hard work, the value of cleanliness, the value of competition. This research is a type of qualitative research with the aim of producing descriptive data in the form of written, spoken words from people and observable behavior in order to provide clarity on the relevance of Islamic da'wah values in the Ngarot tradition in Lelea village, Lelea district, Indramayu district. Data collection techniques in this study used the methods of observation, interviews and documentation. The results of this study explain that the implementation of the Ngarot tradition is carried out on Wednesdays (except Kliwon Wednesday) in December every year. The process is, a parade (parade) around the village of Lelea, the handover of panca usaha tani (five objects that are closely related to agriculture), then ends with artistic entertainment. Among the goals of this tradition is as a form of gratitude for the arrival of the rice planting season. The da'wah values contained in this Ngarot tradition include; First, the value of discipline in the implementation of the Ngarot tradition is reflected in the attitude to be able to protect oneself from adultery and the command to be able to restrain one's lust. Second, the value of honesty in the form of orders to always maintain faith, orders to spread peace, gratitude and orders to do good deeds. Third, the value of hard work which is reflected through the command not to give up. Fourth, the value of competition is reflected through the command of friendship, maintaining togetherness and intelligence.